Pendidikan Karakter Bangsa dalam Pandangan HOS Tjokroaminoto - Fatimatuzzahro, Faza; Lestari, Marselina Ayu; Amirah, Fadhila Syarifatun; Wahyuningsi, Wahyuningsi; Hermawan, Toto (Universitas Cokroaminoto Yogyakarta, 2024)
Basic principles of education in Indonesia have been provided by national figure, HOS Tjokroaminoto. In light of the country's rapidly evolving technology and the emergence of foreign cultures, which have the potential to steadily destroy the nation's morality, this investigation is made to convey his opinions on the necessity of character education in Indonesia. The primary materials for this study, which are his original writings, and secondary sources, which are other people's writings on his ideas, were found through the library research method. To sum up, HOS Tjokroaminoto's character education attempts to improve each person's standing and dignity by incorporating the principles of nationalism, democracy, and equality into the educational process. Character education is the only way to achieve Indonesia's goals, which include forging a civilized and noble national character.